2004
DOI: 10.1016/j.crte.2003.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of eleven years of deformation measured by GPS in the Corinth Rift Laboratory area

Abstract: International audienceGPS (Global Positioning System) data collected in the Corinth Rift during eleven campaigns between 1990 and 2001 provide velocities of 57 points with ∼ 1.5 mmyr−1 accuracy. Peloponnesos moves at 30 mmyr−1 to the N215◦ E with respect to a fixed Europe. Extension across the rift is accommodated in a narrow band offshore. Its rate increases from east to west and is 16 mmyr−1 near Aigion. Both sides of the rift behave as clockwise rotating blocks with rates of 7 ± 0.5◦ Myr−1 and 2.8±0.8◦ Myr−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
154
0
21

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(192 citation statements)
references
References 17 publications
14
154
0
21
Order By: Relevance
“…This accelerated Holocene uplift is also consistent with the observed discrepancy between hiceeding 10 mm year -1 in the central rift according to geodetic measurements (Clarke et al, 1998;Avallone et al, 2004), and much lower long-term rates, smaller than 5 mm year -1 during the last 0.7 Ma in the same area . Furthermore, the intriguing westward increase in GPS-derived extension rates (e.g., Bell et al, 2011) parallels the S R -inferred westward decrease in age of the recent uplift acceleration.…”
Section: Timing Of the Uplift Phasessupporting
confidence: 74%
See 1 more Smart Citation
“…This accelerated Holocene uplift is also consistent with the observed discrepancy between hiceeding 10 mm year -1 in the central rift according to geodetic measurements (Clarke et al, 1998;Avallone et al, 2004), and much lower long-term rates, smaller than 5 mm year -1 during the last 0.7 Ma in the same area . Furthermore, the intriguing westward increase in GPS-derived extension rates (e.g., Bell et al, 2011) parallels the S R -inferred westward decrease in age of the recent uplift acceleration.…”
Section: Timing Of the Uplift Phasessupporting
confidence: 74%
“…In any case, this recent evolution coincides with an apparent increase in modern extension rates. Indeed, GPS measurements in the Corinth gulf area indicate current rates ranging from < 5 mm year -1 at the eastern end of the rift to 11 mm year -1 at the height of Xylokastro and 16 mm year -1 in the western rift (Avallone et al, 2004;Nyst and Thatcher, 2004;Bernard etal., 2006). However, beyond the fact that the E-W variation of these rates does not superpose with long-term variations showing maximum total extension in the central rift (Bell et al, 2011), the question of how, if ever, geologically instantaneous GPS rates may compare with long-term averaged rates is still debated (e.g., Friedrich et al, 2003;Bell et al, 2011).…”
Section: Naf: North Anatolian Faultmentioning
confidence: 99%
“…show that most of present-day deformation is concentrated offshore in a narrow band (Briole et al, 2000;Avallone et al, 2004). In this area, the southern coast is bounded by the en-echelon Eliki-AigionKamarai-Psathopyrgos fault system (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The deformation is currently localized on en-echelon north-dipping normal faults delimiting the southern coastline, as well as on N-and S-dipping offshore faults ( Fig. 1) (Avallone et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This active shallow-dipping crustal-scale shear zone accommodates extension at a shear rate of 1 cm yr −1 , distributed at 10-15 km over a 1 km thick zone (Avallone et al, 2004). Crustal-scale thermo-mechanical models of this detachment have shown that kinematics of high angle normal faults in its hanging wall as well as the observed formation of out-of-sequence faults can only be reproduced for low effective viscosity of the order of 10 19 to 10 20 Pa s within the shear zone (Le Pourhiet et al, 2004) .…”
Section: Geological Motivationsmentioning
confidence: 99%